The Foucault Effect in Argentina (1970-1990) - Canavese, Mariana (2017)
Argentina is one of the central hubs of the Latin American reception of Foucault, where connections with the rest of the region can also be observed. By reconstructing the Argentine reception of Foucault, aspects associated with the transformation of the social sciences and humanities can be analysed, as well their interdependencies with the intellectual and political domains, and, in particular, the circulation and uses of Foucault by non-academic spaces since the late 1950s. The present article first provides a general periodisation of this reception. Then, some of the key elements that join the early restricted circulation (1961-1983) and the later widespread diffusion (1983 to present-day) are explained, in three periods through which one can observe how Foucault operates in very different contexts (State terrorism, debates on Marxism and the crisis of the Argentine left, and the recuperation of democracy); perceive certain uses by Argentine intellectuals and academics in the social sciences and humanities; and analyse the ways in which these are connected to specific ways of interpreting local culture and politics.